Exploring the impact of globalization and economic-energy dynamics on environmental sustainability in the EU - Aura Girlovan; Cristiana Tudor; Gabriel Robert Saiu; Daniel Dumitru Guse (Global Transitions)
This paper investigates the determinants of environmental sustainability by analyzing the impact of various economic, fiscal, and energy-related variables on greenhouse gas (GHG) emissions and energy intensity (EI) across 27 European Union member states from 2005 to 2022. Using dynamic panel data analysis through the system Generalized Method of Moments (GMM) estimator, we explore how key factors such as GDP per capita growth, foreign direct investment (FDI), portfolio investments (PI), trade openness (TO), and stock market performance (SMP) influence environmental outcomes. Additionally, the analysis examines the role of fiscal policies, represented by government deficit/surplus (GDT), and energy-related factors, such as renewable energy consumption (REC) and research and development expenditure (ERD), in shaping sustainability. The findings reveal that while GDP growth correlates positively with increased GHG emissions, it negatively impacts energy intensity, suggesting that economic expansion may drive emissions upward while concurrently promoting greater energy efficiency. Trade openness significantly mitigates GHG emissions, indicating that enhanced international trade facilitates access to cleaner technologies. The effects of FDI and PI present a more ambivalent picture, often associated with elevated GHG emissions in the absence of stringent regulatory frameworks. Notably, renewable energy adoption emerges as a critical driver of sustainability, effectively mitigating the environmental impacts of globalization. This study provides valuable insights into the complex interplay between economic globalization and environmental sustainability, offering actionable policy recommendations to align economic growth with the EU's long-term environmental objectives.